Atypical Charles Bonnet Syndrome - Arun, Priti (Medknow Publications & Media Pvt Ltd, 2013)
Charles Bonnet syndrome (CBS) is not uncommon disorder. It may not present with all typical symptoms and intact insight. Here, a case of atypical CBS is reported where antipsychotics were not effective. Patient improved completely after restoration of vision.